Flipbook and e-learning for teaching English to elementary school teacher education students - Herlina Usman; Ika Lestari; Yulia Elfrida Yanty Siregar; Syarifa Rafiqa Rafiqa; Izlan Sentryo (Studies in English Language and Education, 2024)
The purpose of this study is to investigate the lecturers and students perception of flipbooks and e-learning in enhancing English learning for teacher education students, the influence of technology integration on student-centered pedagogy for teacher education students, and the use of flipbooks and e-learning to improve English skills for teacher education students. Thirty students and nine lecturers from elementary school teacher education programs at three Indonesian universities participated in this study, which used the qualitative descriptive technique. They attend Universitas Halu Oleo Kendari in Southeast Sulawesi, Universitas Borneo Tarakan in North Kalimantan, and Universitas Negeri Jakarta in Jakarta. Data collection was conducted through documents, observations, interviews, and questionnaires. This study found that both lecturers and students positively perceive flipbooks and e-learning as tools for enhancing English learning in elementary school teacher education. Flipbooks effectively present complex concepts, while e-learning provides accessible, diverse resources that develop digital skills. Technology integration significantly benefits student-centered pedagogy but also poses challenges such as technical issues and increased workloads. The study highlighted the need for interventions to improve students listening and speaking skills, suggesting that combining effective teaching methods and digital media can enhance English language proficiency and the overall learning experience. It is suggested that more efforts should be directed toward promoting technology pedagogy content knowledge that fosters students higher-order thinking skills in English teaching materials for elementary school teacher education programs in higher education in Indonesia.